Preclinical Studies of Immunogenity, Protectivity, and Safety of the Combined Vector Vaccine for Prevention of the Middle East Respiratory Syndrome - Dolzhikova, I. V. (Acta Naturae, 2020)
The Middle East Respiratory Syndrome (MERS) is an acute inflammatory disease of the respiratory system caused by the MERS-CoV coronavirus. The mortality rate for MERS is about 34.5%. Due to its high mortality rate, the lack of therapeutic and prophylactic agents, and the continuing threat of the spread of MERS beyond its current confines, developing a vaccine is a pressing task, because vaccination would help limit the spread of MERS and reduce its death toll. We have developed a combined vector vaccine for the prevention of MERS based on recombinant human adenovirus serotypes 26 and 5. Studies of its immunogenicity have shown that vaccination of animals (mice and primates) induces a robust humoral immune response that lasts for at least six months. Studies of the cellular immune response in mice after vaccination showed the emergence of a specific CD4(+) and CD8(+) T cell response. A study of the vaccine protectivity conducted in a model of transgenic mice carrying the human DPP4 receptor gene showed that our vaccination protected 100% of the animals from the lethal infection caused by the MERS-CoV virus (MERS-CoV EMC/2012, 100LD(50) per mouse). Studies of the safety and tolerability of the developed vaccine in rodents, rabbits, and primates showed a good safety profile and tolerance in animals; they revealed no contraindications for clinical testing.